2022
DOI: 10.52403/ijhsr.20220331
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a Psychiatric Nursing Procedure Manual (PNPM) on Psychiatric Nursing Training among the Undergraduate Students in Selected Setting

Abstract: Introduction: Psychiatric nursing teaches students how to engage and communicate with patients who have severe emotional distress. Nurses need this knowledge as the majority of patients encountered in hospitals are distressed Objectives of the Study: To assess the need of the procedure manual for nursing training among UG student nurses before and after the introduction of procedure manual in selected setting. To determine the levels of performance ability and confidence of psychiatric student nurses’ group I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
1
0
0
1
Order By: Relevance
“…241 (79.8%) of the respondents agreed that skill laboratory training helps them understand procedures; 36 (11.9%) disagreed, while 25 (8.3%) were neutral. These findings are consistent with those of [10] who found that 75% of the students thought skills lab training and procedure manuals helped them learn skills and procedures. They add that the skills lab environment encouraged reading in-depth about various themes, encouraged seeing more patients' difficulties, and improved students' writing abilities, in addition to enhancing students' learning by identifying areas of weakness.…”
Section: Perception Levels Among Clinical Officers' Students On the E...supporting
confidence: 91%
See 1 more Smart Citation
“…241 (79.8%) of the respondents agreed that skill laboratory training helps them understand procedures; 36 (11.9%) disagreed, while 25 (8.3%) were neutral. These findings are consistent with those of [10] who found that 75% of the students thought skills lab training and procedure manuals helped them learn skills and procedures. They add that the skills lab environment encouraged reading in-depth about various themes, encouraged seeing more patients' difficulties, and improved students' writing abilities, in addition to enhancing students' learning by identifying areas of weakness.…”
Section: Perception Levels Among Clinical Officers' Students On the E...supporting
confidence: 91%
“…241 (79,8 %) респондентов согласились с тем, что лабораторная подготовка помогает им понимать процедуры; 36 (11,9 %) не согласились с этим, а 25 (8,3 %) заняли нейтральную позицию. Эти результаты согласуются с результатами [10], которые обнаружили, что 75 % студентов считают, что лабораторные тренинги и руководства по процедурам помогли им освоить навыки и процедуры. Они добавляют, что среда лаборатории навыков способ-ствовала углубленному чтению на различные темы, способствовала большему количеству трудностей пациентов и улучшила способности учащихся к письму, в дополнение к улучшению знаний учащихся за счет выявления слабых мест.…”
Section: уровни восприятия студентами клинических специалистов эффект...unclassified